2022
DOI: 10.1371/journal.pone.0273744
|View full text |Cite
|
Sign up to set email alerts
|

Core competencies of peer workers who use pulse oximeters to supplement their overdose response in British Columbia

Abstract: Introduction Peer workers (those with lived/living experience of substance use) are at the forefront of overdose response initiatives in British Columbia, Canada. The onset of the coronavirus disease pandemic has significantly compounded the impact of the overdose crisis. Peer workers are integral in supporting people who use substances. However, despite the important work they do, peer workers often lack formalized credibility and do not have the same resources available to them as service providers without l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…For instance, from an equity lens, oximetry has been shown to be less reliable among people with darker skin tones [ 38 ] and therefore, additional measures to promote safe monitoring may be required for certain ethnic and racial minorities. Our study offers crucial lessons about participatory research strategies: meaningful partnerships with people with lived/living experience of drug use in all aspects of design and implementation [ 39 , 40 ] and capacity-building [ 27 , 41 ] were integral to our success. OPS sites guided necessary steps in study implementation to ensure that our oximetry protocol met the needs of participating OPS clients and staff.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, from an equity lens, oximetry has been shown to be less reliable among people with darker skin tones [ 38 ] and therefore, additional measures to promote safe monitoring may be required for certain ethnic and racial minorities. Our study offers crucial lessons about participatory research strategies: meaningful partnerships with people with lived/living experience of drug use in all aspects of design and implementation [ 39 , 40 ] and capacity-building [ 27 , 41 ] were integral to our success. OPS sites guided necessary steps in study implementation to ensure that our oximetry protocol met the needs of participating OPS clients and staff.…”
Section: Discussionmentioning
confidence: 99%
“…We employed a participatory/community-based design, collaborating with people with lived/living experience of substance use throughout planning, implementation, analysis, and knowledge translation. We held three planning meetings to co-develop procedures and instruments with the Professionals for Ethical Engagement of Peers (PEEP), a BC Centre for Disease Control provincial peer advisory committee [ 27 , 28 ]. We engaged OPS staff to identify site-specific needs and facilitate implementation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finding may re ect the important role people working at OPS and DCS sites play in connecting clients to ancillary harm reduction and treatment services such as PSS. The role of people with lived and living experience of substance use in overdose response in BC must be acknowledged, where many DCS and OPS services rely on the expertise and leadership of people working in what are often termed "Peer worker" roles (41)(42)(43)(44). Studies have demonstrated that Peer workers rely on their informal roles and social networks to develop a sense of trust and safety that cannot be met by nonpeer staff (45).…”
Section: Discussionmentioning
confidence: 99%
“…These types of training have been shown to be an effective strategy to increase skills and helping behaviour in other populations, particularly when structured in a harm reduction context and when delivered in a peer-to-peer format 43. Peer-to-peer interventions are important strategies to address the overdose epidemic, as these programmes help to engage individuals in addressing the overdose epidemic and aid in rebuilding trust in the healthcare system 30 44. Public health professionals should consider implementing naloxone-based training, an important predisposing skill to address potential opioid-related overdoses, in communities substantially impacted by the overdose epidemic in order to equip all members of the community to intervene with bystander or peer-to-peer intervention.…”
Section: Discussionmentioning
confidence: 99%